2011
DOI: 10.1371/journal.pone.0021114
|View full text |Cite|
|
Sign up to set email alerts
|

A Unique Resource Mutualism between the Giant Bornean Pitcher Plant, Nepenthes rajah, and Members of a Small Mammal Community

Abstract: The carnivorous pitcher plant genus Nepenthes grows in nutrient-deficient substrates and produce jug-shaped leaf organs (pitchers) that trap arthropods as a source of N and P. A number of Bornean Nepenthes demonstrate novel nutrient acquisition strategies. Notably, three giant montane species are engaged in a mutualistic association with the mountain treeshrew, Tupaia montana, in which the treeshrew defecates into the pitchers while visiting them to feed on nectar secretions on the pitchers' lids.Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Our results show that the higher altitude species will lose a greater amount of potentially suitable habitat by 2070 compared to the lower species (Table 2). Habitat shifts would need to account for interactions concerned with diet (Moran, 2001;Merbach et al, 2002;Clarke et al, 2009;Greenwood et al, 2011), symbiotic specializations (Bonhomme et al, 2011;Rembold et al, 2012) and pollinators. It is estimated that some habitats may disappear completely as a result of the current and predicted climate change (Williams et al, 2007).…”
Section: Genetic Vs Ecological Divergencementioning
confidence: 99%
“…Our results show that the higher altitude species will lose a greater amount of potentially suitable habitat by 2070 compared to the lower species (Table 2). Habitat shifts would need to account for interactions concerned with diet (Moran, 2001;Merbach et al, 2002;Clarke et al, 2009;Greenwood et al, 2011), symbiotic specializations (Bonhomme et al, 2011;Rembold et al, 2012) and pollinators. It is estimated that some habitats may disappear completely as a result of the current and predicted climate change (Williams et al, 2007).…”
Section: Genetic Vs Ecological Divergencementioning
confidence: 99%
“…11,18 Further, it has been demonstrated that N. rajah pitchers produce volatiles that attract small mammals. 11 The possible role of volatiles in attraction of tree shrews to N. lowii and N. macrophylla pitchers awaits further investigation.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Birds such as Mountain Blackeyes (Chlorocharis emiliae) have also occasionally been observed feeding on the N. lowii lid secretion (Phillipps et al 2008). Nepenthes rajah, another species from the high mountains of Sabah that reportedly attracts tree shrews (T. montana) and summit rats (Rattus baluensis) and captures their faeces (Greenwood et al 2011;Wells et al 2011), shows similar adaptations of its pitcher morphology (Figure 1d). The size and shape of the pitcher opening has been shown to be strongly correlated with the body size of the tree shrews (Chin et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…While most Nepenthes trap insects, some species have recently been shown to engage in mutualistic relationships with vertebrates (Clarke et al 2009;Grafe et al 2011;Greenwood et al 2011). In these exceptional cases, the plant has evolved specific adaptations to attract small mammals.…”
Section: Introductionmentioning
confidence: 99%